Double Day Work: How Women Cope with Time Demands - Suzanna Smith; Diana Converse (EDIS, 2009)
FAR5047, a 2-page transcript of the Family Album Radio Program broadcast by Suzanna Smith and Diana Converse, describes the imbalance between women in the work force and men in the amount of time spent on household duties, and the strategies women develop for combining the demands of work and family. Includes references. Published by the UF Department of Family Youth and Community Sciences, February 2009.